071 Natalizumab extended interval dosing (EID) is associated with a significant reduction in progressive multifocal leukoencephalopathy (PML) risk compared with standard interval dosing (SID) in the touch® prescribing program. Issue 6 (24th May 2018) - Ryerson, Lana Zhovtis; Foley, John; Chang, Ih; Kister, Ilya; Cutter, Gary; Metzger, Ryan; Goldberg, Judith D; Li, Xiaochun; Riddle, Evan; Smirnakis, Karen; Yu, Bei; Ren, Zheng; et al.
Abstract : Introduction: Natalizumab, approved for 300 mg intravenous every-4-weeks dosing, is associated with PML risk. Prior studies have been inconclusive regarding EID's impact on PML risk. The US REMS program (TOUCH) offers the largest data source that can inform on PML risk in patients on EID. This analysis aimed to determine whether natalizumab EID is associated with reduced PML risk compared with SID. Methods: Investigators developed SID and EID definitions and finalised the statistical analysis plan while blinded to PML events. Average dosing intervals (ADIs) were ≥3 to<5 weeks for SID and >5 to≤12 weeks for EID. The primary analysis assessed ADI in the last 18 months of infusion history. The secondary analysis identified any prolonged period of EID at any time in the infusion history. The tertiary analysis assessed ADI over the full infusion history. Only anti-JC virus antibody positive (JCV Ab+) patients with dosing intervals≥3 to≤12 weeks were included. PML hazard ratios (HRs) were compared using adjusted Cox regression models and Kaplan-Meier estimates. Results: Analyses included 13, 132 SID and 1988 EID patients (primary), 15, 424 SID and 3331 EID patients (secondary), and 23, 168 SID and 815 EID patients (tertiary). In primary analyses, ADI (days) was 30 for SID and 37 for EID; median exposure (months) was 44 for SID and 59 for EID. Most EID patients received >2 years SID prior to EID. The PML HR (95% CI) was 0.06 (0.01–0.22; p<0.001) for primary analysis and 0.12 (0.05–0.29; p<0.001) for secondary analysis (both in favour of EID); no EID PML cases were observed in tertiary analyses (Kaplan-Meier log-rank test p=0.02). Conclusion: In JCV Ab +patients, natalizumab EID is associated with a clinically and statistically significant reduction in PML risk as compared with SID. As TOUCH does not collect effectiveness data, further studies are needed. Study support: Biogen